2007
DOI: 10.1111/j.1467-9450.2007.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Automatic semantic priming in the left and right hemispheres

Abstract: We investigated hemispheric differences and inter-hemispheric transfer of facilitation in automatic semantic priming, using prime-target pairs composed of words of the same category but not associated (e.g. skirt-glove), and a blank-target baseline condition. Reaction time and accuracy were measured at short (300 ms) intervals between prime and target onsets, using a go/no-go task to discriminate between word or non-word targets. Reaction times were facilitated more for target words presented in the right visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…At short SOAs, Step 2 n priming occurs more reliably in the RVF-LH (Korsnes & Magnussen, 2007;Collins, 1999;Koivisto, 1997Koivisto, , 1998Abernethy & Coney, 1990 than in the LVF-RH (Bouaffre & Faita-Ainseba, 2007;Koivisto, 1998), for which it is reported between strongly but not weakly overlapping co-exemplars (Grose-Fifer & Deacon, 2004).…”
Section: Priming Effects As a Function Of Soa And Association Strengthmentioning
confidence: 92%
“…At short SOAs, Step 2 n priming occurs more reliably in the RVF-LH (Korsnes & Magnussen, 2007;Collins, 1999;Koivisto, 1997Koivisto, , 1998Abernethy & Coney, 1990 than in the LVF-RH (Bouaffre & Faita-Ainseba, 2007;Koivisto, 1998), for which it is reported between strongly but not weakly overlapping co-exemplars (Grose-Fifer & Deacon, 2004).…”
Section: Priming Effects As a Function Of Soa And Association Strengthmentioning
confidence: 92%
“…In addition, some authors suggest that priming in the LH is based on automatic processing, while priming in the RH is based on controlled postlexical processing (Koivisto and Laine 2000; Koivisto and Hämäläinen 2002). Nevertheless, this interpretation has been often criticized and whether the LH or the RH hemisphere is better adapted for the automatic spreading activation of categorically related words is still a matter for discussion (Chiarello 2000; Korsnes and Magnussen 2007).…”
Section: Behavioral Studiesmentioning
confidence: 99%
“…The right hemisphere has superior abilities in visual-spatial tasks and some specific verbal tasks (Korsnes & Magnussen, 2007;Levy & Kueck, 1986). In addition, Springer and Deutsch (1998) reported that the right hemisphere is superior to the left hemisphere in recognizing geometric shapes.…”
mentioning
confidence: 98%
“…Language and speech abilities have been found to be most prominent in the left hemisphere for right-handed persons (Korsnes & Magnussen, 2007). Even when participants are asked to identify letters, responses are faster for stimuli in the right visual field/left hemisphere (RVF/LH) than when the stimuli are presented to the left visual field/right hemisphere (LVF/RH; Rizzolatti, Umilta, & Berlucchi, 1971).…”
mentioning
confidence: 99%